Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Perawat Pada Bidang Perawatan Dan UGD Di Puskesmas Mamasa - Tirza Juita; M. Ikhwan Maulana; Uhud Darmawan Natsir; Abdi Akbar Idris; Muh. Ilham Wardhana Haeruddin (Universitas Kristen Indonesia Toraja, 2023)
This study aims to determine the influence of motivation on nurse performance, the influence of the work environment on nurse performance and the influence of motivation and the work environment on nurse performance in the nursing and ER fields at the Mamasa Community Health Center. The type of data used in this research is quantitative data obtained from questionnaires distributed and related to the problem being studied with a sample size of 44 people. The research results show that the motivation variable has a significant level of 0.000, which is smaller than 0.05 with a coefficient value of 0.465 indicating that the influence given is positive on the independent variable. The work environment variable has a significance level of 0.000 with a coefficient value of 0.0448 indicating that the influence given is positive on the independent variable